Fabrication of oil–water separation copper filter by spatial light modulated femtosecond laser. (5th May 2020) - Sun, Xiaoyan; Dong, Zhuolin; Cheng, Kaifan; Chu, Dongkai; Kong, Dejian; Hu, Youwang; Duan, Ji'an
Abstract: Surface with oil–water separation performance has attracted more and more attention in the application of oil-containing wastewater purification. Much related work has been done by many researchers. However, there are still many difficulties in rapid manufacturing of filter membranes with special wettability. In this paper, an efficient, flexible method to fabricate microporous arrays by using a femtosecond (fs) laser combined with a spatial light modulator is proposed. The laser treated copper sheet surface shows hydrophobic and superoleophilic properties due to the microstructure. Meanwhile, the array of micro-through-holes on the surface can allow oil to penetrate through holes and prevent water from penetrating. The manufacturing process is not only extremely efficient, with a 10 × 10 focus array used in the ablation, but also it is without chemical method and the filter presents a long-term stable hydrophobic and superoleophilic performance.